Development and Preliminary Validation of a Scale to Measure Perceived Therapist's Knowledge about Gender Identity Diversity among Trans and Non-Binary Individuals in Puerto Rico - Caleb Esteban; Eddiel Hernández-López; Margarita Francia-Martínez; Alixida Ramos-Pibernus (MDPI AG, 2024)
This study aimed to describe the development of the Perceived Therapist's Knowledge about Gender Identity Diversity Scale and to preliminarily validate this scale by describing its psychometric properties. This research instrument was constructed based on the existing literature and recommendations for instrument development. Initially, a 36-item scale was devised to assess perceived openness and knowledge about gender identity diversity in therapy. The content validation process involved 12 expert judges, leading to a refined 25-item scale. Participants consisting of 57 trans and non-binary Puerto Rican individuals completed the scale. Exploratory factor analysis revealed a unidimensional structure, supporting a single factor named "perceived knowledge about gender identity diversity in therapy." The final scale demonstrated excellent reliability (α = 0.978; Sα = 0.980; ω = 0.979), indicating strong internal consistency. This validated scale contributes to assessing primarily Hispanic trans and non-binary individuals' perceptions of their therapists' knowledge about gender identity diversity.